A Review of Modern Radiation Therapy Dose Escalation in Locally Advanced Head and Neck Cancer. Issue 5 (May 2020) - Atwell, D.; Elks, J.; Cahill, K.; Hearn, N.; Vignarajah, D.; Lagopoulos, J.; Min, M.
Abstract: The management of head and neck cancer is complex and often involves multimodality treatment. Certain groups of patients, such as those with inoperable or advanced disease, are at higher risk of treatment failure and may therefore benefit from radiation therapy dose escalation. This can be difficult to achieve without increasing toxicity. However, the combination of modern treatment techniques and increased research into the use of functional imaging modalities that assist with target delineation allows researchers to push this boundary further. This review aims to summarise modern dose escalation trials to identify the impact on disease outcomes and explore the growing role of functional imaging modalities. Studies experimenting with dose escalation above standard fractionated regimens as outlined in National Comprehensive Cancer Network guidelines using photon therapy were chosen for review. Seventeen papers were considered suitable for inclusion in the review. Eight studies investigated nasopharyngeal cancer, with the remainder treating a range of subsites. Six studies utilised functional imaging modalities for target delineation. Doses as high as 85.9 Gy in 2.6 Gy fractions (EQD2 90.2 Gy10 ) were reportedly delivered with the aid of functional imaging modalities. Dose escalation in nasopharyngeal cancer resulted in 3-year locoregional control rates of 86.6–100% and overall survival of 82–95.2%. For other mucosal primary tumour sites, 3-year locoregional control reached 68.2–85.9% and 48.4–54% for overall survival. There were no clear trends in acute or late toxicity across studies, regardless of dose or addition of chemotherapy. However, small cohort sizes and short follow-up times may have resulted in under-reporting. This review highlights the future possibilities of radiation therapy dose escalation in head and neck cancer and the potential for improved target delineation with careful patient selection and the assistance of functional imaging modalities. Highlights: Certain groups of patients with HNC may be at high risk of treatment failure and may benefit from radiation therapy dose escalation. Dose escalation is feasible to at least 10Gy10 above conventionally recommended dose and fractionation. The utilisation of functional imaging modalities in treatment planning may improve outcomes without worsening toxicity rates.